AB0365 The Efficacy and Safety of Abatacept as A First Biologics in Japanese Rheumatoid Arthritis Patients Complicated by Pulmonary Involvement. (15th July 2016) - Takata, M.; Tsunoda, S.; Ogita, C.; Yokoyama, Y.; Abe, T.; Maruoka, M.; Furukawa, T.; Yoshikawa, T.; Tanaka, K.; Saitou, A.; Nishioka, A.; Sekiguti, M.; et al.
Abstract : Background: In clinical practice, it is not rare that we encounter patients with rheumatoid arthritis (RA) complicated by lung involvement. Clinically, lung involvement that accompany RA can be divided into: 1) lung lesions developing as extra-articular symptoms of RA, 2) drug-induced lung lesions caused by the drugs used for RA treatment, 3) opportunistic infection developing during RA treatment, and 4) others including lung lesions without causal relationship to RA. Then, starting the treatment, lung involvement is an important factor to select the disease-modifying anti-rheumatoid drugs (DMARDs) including biologics. There are many unfavorable reports to use tumor necrosis factor-α inhibitor, tocilizumab and rituximab in RA patients with lung involvement. Until now there are few reports whether or not abatacept induced serious respiratory adverse events (SRAE) and exacerbated RA associated ILD (RA-ILD). Objectives: To compare the efficacy and safety of abatacept as a first biologics in RA patients between complicated with and without pulmonary involvement. Methods: This is a prospective observation study. Thirty eight RA patients, who have never used biologics, were enrolled in this study. Pulmonary involvement was evaluated by high resolution computed tomography (HRCT). At 48 weeks after the enrollment of the study, clinical efficacy, safety, and continuation rate were compared between RA patients with pulmonary involvement and without pulmonary involvement. Results: All patients are Japanese and eight patients were male and thirty patients were female. The mean age was 59.0±14.1 year-old, the mean prednisolone dose was 3.89±3.35 mg/day, and the mean methotrexate dose was 5.37±3.78 mg/week. DAS28-CRP was 4.24±1.33 and SDAI was 24.01±12.32 at enrolment. Eleven patients showed pulmonary involvement (8 patients: airway disease, 3 patients: interstitial lung disease). At 48 weeks, SDAI was significantly improved in both group (patients with pulmonary involvement: 25.3±14.56 to 14.23±12.31; p=0.023, patients without pulmonary involvement: 23.48±11.55 to 7.69± 6.70; p<0.001). ΔDAS28-CRP was no significant difference between patients with pulmonary involvement and without pulmonary involvement (mean change, -1.20 vs -1.81; p=0.47). There was no change in LDH and KL-6 level in both group. Continuation rate was 81.6% and there was no difference between patients with pulmonary involvement (90.0%) and without pulmonary involvement (77.8%). There were no patients with exacerbating interstitial lung disease. Conclusions: Abatacept as a first biologics is safe and effective in RA patients regardless of the presence or absence of pulmonary involvement. Furthermore abatacept did not lead the exacerbation of the existing pulmonary involvement. References: Jani M, et al. Nat Rev Rheumatol 2014; 5: 284 Curtis JR, et al. Arthritis Research & Therapy 2015; 17: 319 Yun H, et al. Ann Rheum Dis 2015; 74: 1065 Acknowledgement: Disclosure of Interest: None declared